Multiwavelength Random Fiber Laser Using Dual Bidirectional Semiconductor Optical Amplifiers and PMF-based Mach-Zehnder Interferometer - Lah A.A.A.; Sulaiman A.H.; Aliza H.E.M.; Yusoff N.M.; Ambran S.; David A.P.; Salleh M.S. (Institute of Electrical and Electronics Engineers Inc., 2024)
A multiwavelength random fiber laser (MWRFL) is successfully demonstrated for the first time from random distributed feedback generated by a spool of single-mode fiber (SMF) and using two semiconductor optical amplifiers (SOAs) in bidirectional configuration together with a Mach-Zehnder interferometer (MZI) based on polarization maintaining fiber (PMF) in a ring cavity. The generated MWRFL has an 80 mA lasing threshold with a slope efficiency of 1.24%. The lasing peak power is -19.1 dBm with an extinction ratio (ER) of 11.6 dB. The MWRFL produced 50 lasing lines within a lasing flatness of 3 dB bandwidth with a channel spacing of 0.22 nm. The MWRFL performance can be increased or decreased by tuning the polarization controller (PC) plate angle, resulting in a variation of the number of lasing lines and ER value. With proper PC plate tuning, the ER value can be increased by up to 61%. The MWRFL has high stability with peak power deviations of 1.2 dB and wavelength fluctuations of 0.4 nm in 120 minutes. 2023 IEEE.